-3(3x-1)+2(5x-4)=16

Simple and best practice solution for -3(3x-1)+2(5x-4)=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3x-1)+2(5x-4)=16 equation:


Simplifying
-3(3x + -1) + 2(5x + -4) = 16

Reorder the terms:
-3(-1 + 3x) + 2(5x + -4) = 16
(-1 * -3 + 3x * -3) + 2(5x + -4) = 16
(3 + -9x) + 2(5x + -4) = 16

Reorder the terms:
3 + -9x + 2(-4 + 5x) = 16
3 + -9x + (-4 * 2 + 5x * 2) = 16
3 + -9x + (-8 + 10x) = 16

Reorder the terms:
3 + -8 + -9x + 10x = 16

Combine like terms: 3 + -8 = -5
-5 + -9x + 10x = 16

Combine like terms: -9x + 10x = 1x
-5 + 1x = 16

Solving
-5 + 1x = 16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 1x = 16 + 5

Combine like terms: -5 + 5 = 0
0 + 1x = 16 + 5
1x = 16 + 5

Combine like terms: 16 + 5 = 21
1x = 21

Divide each side by '1'.
x = 21

Simplifying
x = 21

See similar equations:

| 3(8)+y=-8 | | ×=-5/7y=14/17 | | 64+32+h=180 | | 9/3.5 | | 3(7)+y=-8 | | n+11=2n+18 | | 3(6)+y=-8 | | 5(-2x-6)=8x | | 1/3x-3y | | 3(4)+y=-8 | | 9y-3(y+4)=12 | | (2p+15)+(p+15)+p=180 | | 6/8=x/x-4 | | 2x+5-x-5=0 | | 3(2x+1)=30x+20 | | 3(3)+y=-8 | | 7x+7y=135+2x+2y | | 2x^4-15x^2+28=0 | | 2p+15+p+15+p=180 | | 48=4x-2(-26+8x) | | 2+q=4.5 | | 82+49+z=180 | | 53-2x=3x-175 | | 5x+8+4x=2x-13 | | 4/5x-3=21 | | h(t)=-16t^2+8t+10 | | 27-2n=17 | | 2fx-g=k | | xsquared-5x+6=0 | | F(x)=x^2-14x+10 | | 4(3.14)216= | | (7a+12b-6c-8)(4)= |

Equations solver categories